Formulation and Comparison of Herbal Gels Containing Essential Oils and their Antimicrobial Evaluation - Agrawal, Karan; Vibha; Murti, Yogesh; Agrawal, Migul; Kulshreshtha, Mayank (Infectious Disorders - Drug Targets, 2025)
ObjectiveThe current study aimed to formulate and evaluate herbal gels containing essential oils for the treatment of infection caused by microbial species, i.e., S. aureus, E. coli, P. aeruginosa, and B. subtilis. These species are also responsible for acne directly and indirectly.Material and MethodsThe gels were prepared using a gelling agent with 1% Carbopol-940, and they were further evaluated for physical appearance, drug content, in-vitro drug release, viscosity, extrudability, pH, and spreadability. Further, anti-microbial screening was done with various microbial species.ResultsStudies revealed that the gel was highly effective against the selected species except for the fungal strain. ZOI was observed ranging from 3.1 ± 0.01 mm to 13.4 ± 0.14 mm. The maximum ZOI was observed at 13.4 ± 0.14 mm against S. aureus. The physical properties of the gel satisfied the standard parameters.ConclusionThe prepared herbal gel was found to have highly promising activity against bacterial species associated with bacterial infection but in a dose-dependent manner. However, more research is required.
Keywords: drug content